Algorithm of video object segmentation based on region Gibbs potential function - BAO Hong-qiang; ZHANG Zhao-yang (Tongxin xuebao)
A novel video motion object segmentation algorithm was proposed under spatial-temporal framework. First, the inter-frame image was partitioned into some regions by the improved watershed algorithm, and the initial segmentation mask was obtained after combining the spatial and temporal segmentation results. Then a model of Markov random field was built based on regions, and the corresponding Gibbs potential energy function was defined. The optimization of solution was carried out by iterated conditional mode （ICM） method. The experiment results show that the algorithm is more effective than COST 211 analysis model.